Ossifying fibromyxoid tumor of the nasal septum - Blum, Andreas; Back, Walter; Naim, Ramin; Hörmann, Karl; Riedel, Frank (Auris, nasus, larynx, 2006)
The fibromyxoid tumor is quite a rare soft tissue tumor and typically presents as an ossifying fibromyxoid tumor (OFMT) in the subcutis of the extremities of adults. Most authors favour schwannian or chondroid origin of this lesion with somehow uncertain biologic dignity. Local recurrence is seen in 27% of patients after primary excision. We present a case of a fibromyxoid tumor of the nasal septum in a 49-year-old female who complained of nasal airway obstruction and enlargement of the right contour of the nose. Endonasal, endoscopic tumor excision was performed. The tumor contained spindle-shaped and polygonal cells, mucoid pseudocysts and a fibromyxoid stroma with local calcifications. The clinical behaviour of OFMT in general is benign but some reports have documented atypical tumors with histologic signs of malignancy. Complete local resection is the treatment of choice. Because of the high rate of local recurrence, clinical follow-up examinations are necessary.